Politics and cultures of liberation : media, memory, and projections of democracy - Bak, Hans; Mehring, Frank, 1970-; Roza, Mathilde Helene, 1968- (Radboud studies in humanities, 2018)
This book focuses on mapping, analyzing, and evaluating memories, rituals, and artistic responses to the theme of "liberation." How is the national framed within a dynamic system of intercultural contact zones highlighting often competing agendas of remembrance? How does the production, (re)mediation, and framing of narratives within different social, territorial, and political environments determine the cultural memory of liberation? The articles compiled in this volume seek to provide new interdisciplinary and intercultural perspectives on the politics and cultures of liberation by examining commemorative practices, artistic responses, and audio-visual media that lend themselves for transnational exploration. They offer a wide range of diverse intercultural perspectives on media, memory, liberation, (self)Americanization, and conceptualizations of democracy from the war years, through the Cold War era to the 21st century